Peripheral Lesion Finding Discrepancies between Ultra-Widefield and Simulated 50° Fluorescein Angiography in Uveitis - Wulandari, Rina; Nora, Rina La Distia; Edwar, Lukman (International Journal of Retina, 2026)
Introduction: With the advance of ultra-widefield fundus imaging, its usefulness for fluorescein angiography study compared to the conventional (50°) for uveitis management is not fully studied. We aimed to compare ultra-widefield fluorescein angiography (UWFFA) and simulated conventional (50°) FA in terms of peripheral fundus findings and its correlation with clinical activity and therapeutic decision changes in uveitis cases. Methods: We performed a descriptive retrospective study in uveitis patients who underwent UWFFA (Optos P200DTx California) in March-May 2021. We compared the presence of peripheral abnormalities between UWFFA images and its simulated 50° FA. We correlated them with clinical uveitis activities and therapeutic decision changes by two uveitis experts. Results: We included 12 uveitis patients and found that 44.4% of peripheral vascular leakage, 83.3% of the peripheral lesion, and 100% of peripheral neovascularization in UWFFA were missed in simulated 50° FA. From 5 clinically inactive patients, 4 out of 5 were assessed as active uveitis on simulated 50° FA interpretation, and all the inactive patients were active uveitis based on UWFFA. 1 out of 12 had a diagnosis and therapeutic changes after UWFFA. Conclusions: We found more peripheral findings in UWFFA than in conventional ones. This discrepancy could alter clinical activity and therapy decisions, and long-term studies are needed to assess the clinical benefit.